ANALISIS KEBIJAKAN PROGRAM KAMPUS MERDEKA DARI KEKERASAN SEKSUAL DI PERGURUAN TINGGI INDONESIA - Purnika Sari, Nia Nia Juwita; Hermawati, Kiki Ayu; Akbar, Muhammad Fikri Rizqi; Sabililhaq, Irhas; Yusuf, Muhamad Hani (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2024)
This study aims to examine the policy of the free campus program from sexual violence in Indonesian universities. The method used is a qualitative method with a literature study approach. The data sources obtained from this paper are journals, books, articles, and other documents that have relevance to the object under study. The author conducts content analysis of the data critically referring to Pancasila and the Law so as to obtain a conclusion. The result of this study is that the independent campus policy on sexual violence has a problem in policy making, because there are articles that seem to legalize adultery. The impact of sexual violence on victims of sexual violence can experience psychological disorders, emotional disorders, behavioral disorders, or cognitive disorders are possible manifestations of this condition. The emotional disturbance in question adversely affects mood and is an unstable emotion. The victim's behavior can then develop into additional negative habits, including extreme lethargy, which is a sign of behavioral problems.